Energy Security: An Important Factor in Global Perspectives - Daniel N. Fita; Florin G. Popescu; Dragos Pasculescu; Emilia Grigorie; Cristina Pupaza; Teodora Lazar (New Trends in Physical Science Research Vol. 3, 2022)
Energy security is included in the idea of a state’s national security, along with industrial, food, sociological, environmental, and sustainable development, information, cyber, economic, defence, and national order security, among other things. The ability of a state to collect resources internally and gain or keep access to external economic resources determines its level of security. The term “energy security” is used almost everywhere in economic and political discussions related to energy supply. However, different authors use different meanings to express the concept of energy security. Mostly, energy security is considered in the dichotomy concerning economic security at the international, as well as national levels. For the purpose to ensure the stability of national and Euro-Atlantic security, the following factors are proposed by authors to achieve and ensure energy security: 25 proposed way to achieving energy security; 8 proposed way to ensuring energy security, and 9 proposed scenarios to quantification energy security almost complete. The final conclusion is: the energy security of a state is in fact the national security of that state. The lack of energy supply (primary energy resources or electricity) of final consumers leads to the onset of crises that cause societal imbalance causing extreme damage to the safety of citizens, industry, the national economy and thus national security, because all sectors of a state economy depend on primary energy resources or electricity.